Malaysia history makers / Mazlina Mustafa Kamal - Mazlina , Mustafa Kamal (2004)
Malaysia History Makers - MhM is an educational software regarding prominent people(Royalty, Prime Ministers, Political Makers, Business Makers, Military Makers, Entertainment Makers and Sport Makers) in Malaysia. It is a Stand-alone tools that contains c.The main goal of MhM development is to provide an educational software that give benefits to all the users specifically on history education in interactive ways of learning. The contents are accurate on comprehensive based on authoritative resources on the selected Malaysian historical figures.The development methodology used was waterfall model. The waterfall model methodology has a clear step-by step phase where the phase is required to be completed almost flawless before proceeding to the next phase besides have greater chances of project delivery on time and within budget.Macromedia Director 8 has been chosen in order to produce a high quality software. With the combination of multimedia development tools such as Adobe Photoshop 7.0 and Macromedia Flash 5.0 the software come out as an interactive learning tool.